Chicana Foundation 1993 - Workshop for Latina Educational Advancement, San Jose City College - Castellano, Alcario:::creator::::::::::::
[No sound]. Video of a workshop for Latina Educational Advancement, sponsored by the Chicana Foundation of Northern California and San Jose City College's Adelante Program and Latino Education Association.